Differential response of cowpea lines to application of P fertilizer - Kolawole, G.O.; Tian, G.; Singh, B.B. (2002)
Phosphorus is important for cowpea production in many tropical African soils with inherent low P fertility. Most farmers in Africa, however, do not have access to P fertilizer. Selection of cowpea lines that produce good yield under low soil P or those with high P-use efficiency can be a low input approach to solving this problem. Pot and field trials were conducted at the International Institute of Tropical Agriculture (IITA), Ibadan, southwestern Nigeria, to assess the differ ential P responses of cowpea lines obtained from the germplasm collection at IITA. Thirty-five lines were assessed for P response in a pot trial using surface (0-15 cm) soil of a P-deficient Alfisol (Oxic Palcustalf). Seventeen lines (com prising of 1 2 lines selected from the pot trial and five not included in the pot trial) were further assessed in the field. In the pot trial, P fertilizer significantly enhanced shoot, root, and grain dry weights. More than 60% of the cowpea lines also had greater nodule weight with P. Response of some of the cowpea lines was more pronounced for shoots than roots. In the field trial, more than 50% of the cowpea lines showed significant response to P. Compared with the pot trial, there were considerable variations in the pattern of responses of the cowpea lines to P. The cowpea lines were classified on the basis of their dry grain weights in the pot trial into four groups. Based on our results, we recommend that lines IT 90K- 284-2, IT 96D-724, and IT 93K-637-1 can be selected for further testing without P fertilizer. Lines IT 87D-94 1 - 1 , IT 86D-7 1 9, and Dan Ila may perform very well without P fertilizer and give a high return when P is applied. When P fertilizer is available, line IT 87D-941 -1 is recommended. These varieties should be tested at multiple sites to truly extend the results to breeding cowpea lines that could be targeted towards various soil P conditions.